Analysis of the Use of I-Nindya Digital Workplace in the Mailing System at PT X - Marghifa, Erikha Ardya; Christian Wiradendi Wolor; Maulana Amirul Adha (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research was conducted with the aim of finding out the use of the application, the effectiveness of the application, as well as the barriers that occur in using the mailing system in the I-Nindya Digital Workplace application. This research design uses qualitative research with a case study approach to provide a comprehensive overview of the use of the I-Nindya Digital Workplace application in the mailing system. The research sample selection technique uses a non-probability sampling method with a purposive sampling method. Data collection techniques were carried out using several methods, namely observation, interviews and documentation. Meanwhile, data validity techniques were carried out using the triangulation method. The results of this research indicate that the use of I-Nindya Digital Workplace in the correspondence system has not been fully implemented in a systematic manner. The effectiveness of using the I-Nindya Digital Workplace application is effective and quite satisfactory in helping to make correspondence work easier. However, this application has not been used optimally by all human resources in the company. Barriers to using I-Nindya Digital Workplace in the mail system are caused by human resource factors and features in the application. One solution to overcome these barriersis to carry out routine application maintenance. Therefore, it is hoped that the results of this research can provide suggestions and input regarding the use of I-Nindya Digital Workplace in the mailing system for future improvements.